P166 Multimorbidity in SLE, a barrier to clinical trial eligibility: results from the BILAG-BR. (26th April 2021) - Dyball, Sarah; Collinson, Sophie; Sutton, Emily; McCarthy, Eoghan; Parker, Ben; ,; Bruce, Ian
Abstract: Background/Aims   Stringent inclusion and exclusion criteria are employed in SLE clinical trials. Organ dysfunction and co-morbidities are common exclusion criteria which may affect how representative trials are of real-world SLE populations. We aimed to apply published trial eligibility criteria to patients with SLE in a large national register. Methods   A literature review of all major published double-blinded randomised phase III trials in non-renal SLE was performed. Common inclusion and exclusion criteria were applied to all patients recruited to the BILAG-Biologics Register (BILAG-BR), a large UK-wide register of SLE patients. Data on comorbidities for all patients registered was collected. The mean (SD) number of co-morbidities was calculated. Patients were then classified as being eligible or ineligible. Groups were compared initially using a chi-squared or Wilcoxon rank-sum test and logistic regression model was used to test the age and sex adjusted association between trial eligibility and comorbidities. Results   Common inclusion and exclusion criteria were identified from 12 published trials. When applied to the 837 patients recruited to BILAG-BR, 562 (67%) patients would not be eligible for inclusion in these trials. Ineligible patients had a shorter disease duration (2.9 vs. 5.1 years, p < 0.01), but were similar in age (P = 1.0), sex (P = 0.7) and ethnicity (p = 0.5) to those who were eligible. Of eligible patients, 128 (53%) had 1 or more comorbidities compared with 340 (60%) who were ineligible (p = 0.05). The mean (SD) number of comorbidities was 0.9 (1.2) vs 1.2 (1.3) for eligible and ineligible patients respectively. After adjusting for age and sex, inclusion in clinical trials was associated with fewer comorbidities (OR 0.81, 95% CI 0.70, 0.94, p < 0.01). Conclusion   Patients with multi-morbidity are more likely to be ineligible for SLE clinical trials. Evidence from real world studies and registers are therefore needed to fully understand the safety and effectiveness of new therapies. Our data also underscores the need to develop more pragmatic eligibility criteria for clinical trials. Disclosure   S. Dyball: None. S. Collinson: None. E. Sutton: None. E. McCarthy: None. B. Parker: Consultancies; GSK, AstraZenica, UCB, Abbvie, Pfizer, BMS, Celltrion. Grants/research support; GSK, Sanofi Genzyme. I. Bruce: Consultancies; GSK, Medimmune, AstraZenica, Eli Lilly, Merck Serono, UCB, ILTOO. Member of speakers' bureau; AstraZeneca, Medimmune, GSK, UCB. Grants/research support; GSK, Genzyme Sanofi, UCB.